Response of growth and drought tolerance of Pterocarpus indicus Willd. seedlings to arbuscular mycorrhizal fungi - Husna Husna; Faisal Danu Tuheteru; Muh. Sandi Juniawan; Basrudin Basrudin; Asrianti Arif; Albasri Albasri; Ikraeni Safitri; Sedek Karepesina (Journal of Tropical Mycorrhiza, 2022)
Drought is one of the environmental factors that can inhibit plant growth and production. Arbuscular mycorrhizal fungi (AMF) were reported to increase plant growth and tolerance to drought stress. Pterocarpus indicus seedlings were inoculated with three AMF treatments (control, Clarodeoglomus. etunicatum, and Septoglomus constrictum) at three watering intervals (watering every day, every two days, and three days) on a greenhouse scale. The results showed that the interaction of C. etunicatum and S. constrictum at various watering intervals effectively increased the height growth of Angsana seedlings. C. etunicatum and S. constrictum and daily watering each increased the diameter of the seedlings. The dry weight of seedlings and the number of root nodules of Angsana seedlings increased in various AMF treatments under daily watering conditions and tended to decrease with watering intervals. Local AMF has the potential to be developed to support the reforestation and conservation of the Angsana species in various land conditions, especially dry land